1979
DOI: 10.1111/j.1365-2672.1979.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the Deep Tissues of Carcasses by Bacteria Present on the Slaughter Instruments or in the Gut

Abstract: Possible routes by which bacteria might reach the deep tissues of carcasses were tested by placing genetically 'marked' strains of Escherichia coli, Clostridium pe$ringens or Bacillus thuringiensis on slaughter instruments before use and examining deep tissue samples for their presence post morteem. Bacteria present on the captive bolt pistol were recovered from the spleens of beef cattle and those placed on the pithing rod were found in both spleen and muscle of the flank and neck. Bacteria from the throat cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 27 publications
(20 reference statements)
4
20
1
Order By: Relevance
“…However, even if the potential for meat contamination from the sticking knife has been shown under laboratory conditions, the risk of such transfers, especially for pathogens like Salmonella and pathogenic E. coli, under commercial conditions seems to be quite low. Mackey and Derrick (1979) reported that in order to induce contamination of the deep tissues of a carcass a large inoculum of 10 10 to 10 12 bacteria was required, whereas the actual level of contamination generally encountered in slaughterhouses is many orders of magnitude less. In a study conducted on bovine hides at a beef slaughter plant in Ireland, hide contamination by E. coli O 157 was reported to be as low as 100 cfu per 100 cm 2 or less in 90.8% of 109 cattle (O'Brien et al, 2005).…”
Section: Cattle Stickingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if the potential for meat contamination from the sticking knife has been shown under laboratory conditions, the risk of such transfers, especially for pathogens like Salmonella and pathogenic E. coli, under commercial conditions seems to be quite low. Mackey and Derrick (1979) reported that in order to induce contamination of the deep tissues of a carcass a large inoculum of 10 10 to 10 12 bacteria was required, whereas the actual level of contamination generally encountered in slaughterhouses is many orders of magnitude less. In a study conducted on bovine hides at a beef slaughter plant in Ireland, hide contamination by E. coli O 157 was reported to be as low as 100 cfu per 100 cm 2 or less in 90.8% of 109 cattle (O'Brien et al, 2005).…”
Section: Cattle Stickingmentioning
confidence: 99%
“…In an experimental study (Mackey & Derrick, 1979), it was demonstrated that microbial contamination of bovine carcasses can occur during sticking. Marked strains of E. coli, Cl.…”
Section: Cattle Stickingmentioning
confidence: 99%
“…With the exception of external surfaces of the animal and the gastro-intestinal and respiratory tracts, the musculature of healthy living animals is free of micro-organisms (Mackey and Derrick, 1979). Once the animal is slaughtered, however, the internal defence mechanisms that combat infectious agents in the living body are lost.…”
Section: Origin Of Micro-organisms In Meatmentioning
confidence: 99%
“…Instead, the incidence of human salmonellosis has been steadily rising for many years, while meat-associated organisms such as Campylobacter and enteropathogenic Escheichia coli have emerged as important causes of enteric disease (Silliker 1982;Griffin et al 1988;Griffiths and park 1990;Park et al 1991 (Gill 1979). Slaughtering will not lead to the contamination of tissues, except when they are directly contacted by slaughtering instruments (Mackey and Derrick 1979). Contamination of meat occurs during the dressing process, when bacteria are transferred from the skins and the guts of carcasses to the freshly exposed meat surfaces.…”
Section: The Efftcacy Of Traditional Meat Inspectionmentioning
confidence: 99%